Buddhism in the Post-Soviet Religious Marketplace. - Clay, J Eugene (Journal of Church & State)
One thing, however, was certain: the state had decided to intervene in Russia's religious economy to ensure that large, politically reliable, "traditional" religions would have an advantage in post-Soviet Russia. 8 For example, in 2007, President Vladimir Putin denied that Russia was a secular state: "The law states that Russia has four traditional religions. Beginning in 1979, Soviet authorities actively courted the Dalai Lama (the spiritual leader of the Gelug school of Tibetan Buddhists) who visited the USSR four times, in 1979, 1982, 1986, and 1991.[34] In 1985, when Mikhail Gorbachev came to power and initiated a democratization of the Soviet Union, there were still only two legally recognized Buddhist communities in all of the USSR. [7] Although the law suggested that many religions might be worthy of special consideration based on these criteria, the list of Russia's "traditional" religions was quickly limited to only four: Orthodox Christianity, Islam, Buddhism, and Judaism.[8] As a practical matter, religious organizations with a continuous legal existence for the previous fifteen years (i.e. since 1982, when Russia was under Soviet atheist rule) were favored in the new, complex process of registration.